Characteristics of Gastroesophageal Reflux Disease (GERD) Patients at RSUP Dr. M. Djamil Padang Period 2018-2021 - Setiawan, Mentari Adinda; Fasrini, Ulya Uti; Amir, Arni; Muchtar, Masrul; Miro, Saptino; Endrinaldi, Endrinaldi (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2023)
Background: Gastroesophageal reflux disease (GERD), a common digestive problem, is increasing and affecting the individual’s quality of life. This study aimed to describe the characteristics of GERD patients at Dr. M. Djamil Central General Hospital.Method: This cross-sectional study used data from patients' medical records that involved 111 GERD patients, excluding chronic disease and pregnancy. The analysis used univariate analysis and performed the data in cross-tables.Results: The results indicated that demographically, nearly all of the samples fall within the range of productive age (94.59%), with a higher proportion of the female gender (54.05%), the majority having a middle education level (72.08%), being housewives (27.92%), and residing in Padang City (35.13%). Most of the main symptoms were heartburn (62.16%), followed by vomiting, nausea, and dysphagia (4.50%, 2.70%, and 1.80%). More patients received outpatient treatment with two visits (18.02%). Clinically, based on the BMI, the obese classification was higher (43.25%). The levels of triglycerides and total cholesterol in the blood of GERD patients were more in the normal category (60.60% and 61.80%), while the levels of HDL and LDL in the blood of GERD patients were in the abnormal category, with lower HDL (97.80%), and a higher LDL (72.70%).Conclusion: The majority of GERD patients were in the productive age group, female, middle level of education, housewives, and resided in Padang. Clinical characteristics of GERD patients included most were categorized as obese according to their BMI, main symptom heartburn, and treated as an outpatient. Triglyceride and total cholesterol were primarily normal; blood HDL and LDL were abnormal.